Screening of Selected Sri Lankan Seasonal Fruit Extracts for Total Antioxidant Activity in vitro - Fernando, Amarosige Shanoli Kavindya; Attanayake, Anoja Priyadarshani; Jayatilaka, Kamani Ayoma Perera Wijewardena (Asian Journal of Pharmaceutical Research and Development, 2019)
The present study aimed to determine the total polyphenol content and total antioxidant activities of ten selected seasonal fruit extracts grown in Sri Lanka. The aqueous refluxed fruit extracts (4h) were used at the initial concentration of 0.05 g/mL. The total polyphenol content was determined according to the Folin-Ciocalteu method. The total antioxidant activity was evaluated by DPPH (2, 2-diphenyl-2-picrylhydrazyl), FRAP (ferric reducing power) and TBA (thiobabituric acid assay) assays with L-ascorbic acid as the reference compound. The total polyphenol content of the fruit extracts varied from 0.81±0 to 17.54±0.50 mg GAE (gallic acid equivalents) per gram of dry weight. The antioxidant activities ranged in IC50 of 46.60±0.60 to 367.90 ± 4.90 μg/mL, 3.41±0.02 to 50.46±1.02 µM, 30.62±0.50 to 182.64±0.90 mg AAE (L-ascorbic acid equivalents) per gram of dry weight for DPPH, FRAP, TBA assays, respectively. All aqueous fruit extracts exert dose dependent in vitro antioxidant activities in different degrees. Among the selected fruit extracts S. carophylatum, P. zeylanica, A. comosus exert relatively high total antioxidant activity together with high total polyphenol content. Hence, the selected fruit extracts are deserved to be as potent sources for antioxidant lead compounds in the development of nutraceuticals using the above edible fruits.